1971
DOI: 10.1177/106939717100600402
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Methods, Functional Associations, and Galton's Problem: A Replicative Assessament 1

Abstract: Sixteen independent tests of the relationship between technological adap tation and settlement patterns provided material for testing sample methods and the interdependence of cases or Galton's problem. Our hypothesis that societies dependent upon agriculture tend to have fixed settlement patterns was strongly confirmed. Linked pair tests for Galton's problem indicated that sample neighbor scores were frequently similar, and we con cluded that these traits were hyperdiffusionally associated. A test for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
1977
1977

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The present analysis thus generally supports the findings of our earlier investigations (Bourguignon 1968(Bourguignon , 1973(Bourguignon , 1974. Also, like a number of other sociocultural traits, such as societal complexity, political integration, stratification, subsistence economy, mode of marriage and others (Naroll 1961;Naroll and D'Andrade 1963;Driver and Schuessler 1967;Barry 1968;Murdock and White 1969;Schaefer et al 1971;Bourguignon and Greenbaum 1973;Murdock and Provost 1973;Evascu 1974) trance type is found to be both 1) semidiffusional, and 2) nonrandomly distributed, or regionally localized within major geographic areas of the world. Furthermore, as in our earlier research, we have found considerable variation in correlations when the worldwide sample is divided into six regional samples.…”
Section: Discussionmentioning
confidence: 95%
“…The present analysis thus generally supports the findings of our earlier investigations (Bourguignon 1968(Bourguignon , 1973(Bourguignon , 1974. Also, like a number of other sociocultural traits, such as societal complexity, political integration, stratification, subsistence economy, mode of marriage and others (Naroll 1961;Naroll and D'Andrade 1963;Driver and Schuessler 1967;Barry 1968;Murdock and White 1969;Schaefer et al 1971;Bourguignon and Greenbaum 1973;Murdock and Provost 1973;Evascu 1974) trance type is found to be both 1) semidiffusional, and 2) nonrandomly distributed, or regionally localized within major geographic areas of the world. Furthermore, as in our earlier research, we have found considerable variation in correlations when the worldwide sample is divided into six regional samples.…”
Section: Discussionmentioning
confidence: 95%